Upper bound Estimates of Fourth Order Hankel and Toeplitz Determinants for Certain Analytic Functions Connected with Three Leaf Function - Rangu, Rudrani; Rayaprolu, Bharavi Sharma; Siginam, Sambasiva Rao (Communications in Mathematics and Applications, 2025)
The purpose of this paper is to compute upper bounds of Hankel and Toeplitz determinants up to fourth order for some normalized univalent functions defined on the open unit disk in the complex plane associated with three leaf function. Suitable examples are provided in support of proven results.